تأثير الضغوط المؤسساتية في جودة معلومات المحاسبة الحكومية - دراسة تجريبية على الجهات العامة ذات الطابع الإداري: The Impact of Institutional Pressures on the Quality of Government Accounting Information: An Empirical Study on Public Administrative Entities - ساميا احمد داود,; روان محي الدين سليمان, (Journal of North African Economies, 2025)
This study aims to examine the impact of institutional pressures—including coercive, normative, and mimetic pressures—on the quality of governmental accounting information. The research assumes that these pressures have a positive influence on the quality of such information. To test this hypothesis, data was collected through a survey distributed to 70 administrative accountants and professionals working in auditing and expenditure divisions within public sector entities in Tartous. The collected data was systematically analyzed using SPSS 26. The findings indicate that institutional pressures positively affect the quality of governmental accounting information, with coercive pressure proving to be the most influential factor. Based on these results, discussions were conducted, and recommendations were formulated to further enhance the quality of governmental accounting practices. Keywords: Institutional Pressure, Coercive Pressure, Normative Pressure, Mimetic Pressure,